2005
DOI: 10.1158/1078-0432.ccr-04-1680
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Papillomavirus Infection in Patients with Colorectal Cancer

Abstract: Purpose: Infection with human papillomaviruses (HPV) is associated with the development of cervical cancer, but whether HPVs have a role in colorectal cancer remains controversial. Experimental Designs: To determine the relationship between HPV and colorectal cancer, we did a retrospective, controlled study using tumor and tumor-adjacent colorectal tissues dissected from patients with colorectal cancer, as well as colorectal tissues from control individuals with no cancer.The samples were processed in a blinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
147
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(165 citation statements)
references
References 22 publications
8
147
1
9
Order By: Relevance
“…Gillison and Shah (2003) indicated that HPV associated malignancies would occur at anatomic subsites of exposure by direct contact, since there is no viremic phase in the pathogenesis of HPV, so the infection is not widely disseminated in the body. On the other hand, Bodaghi et al (2005) reported that HPV infection in the tumor tissues which obtained from the cecum and ascending is as common as in the tissues obtained from rectosigmoid locations and this indicated the HPV infection might not be a result of the direct spread from anogenital sites, also Chen et al (2012) found that the transmission of the HPV to the colorectal tissues might occur through blood circulation. Since higher frequency of HPV infection in cecal and ascending tissues has been determined in compare to frequency of infection in rectosigmoid tissues, this study supports the hypothesis that investigated HPV infection in colon and rectum might not occurs through direct infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gillison and Shah (2003) indicated that HPV associated malignancies would occur at anatomic subsites of exposure by direct contact, since there is no viremic phase in the pathogenesis of HPV, so the infection is not widely disseminated in the body. On the other hand, Bodaghi et al (2005) reported that HPV infection in the tumor tissues which obtained from the cecum and ascending is as common as in the tissues obtained from rectosigmoid locations and this indicated the HPV infection might not be a result of the direct spread from anogenital sites, also Chen et al (2012) found that the transmission of the HPV to the colorectal tissues might occur through blood circulation. Since higher frequency of HPV infection in cecal and ascending tissues has been determined in compare to frequency of infection in rectosigmoid tissues, this study supports the hypothesis that investigated HPV infection in colon and rectum might not occurs through direct infection.…”
Section: Discussionmentioning
confidence: 99%
“…(2011) and Burnett-Hartman et al (2013), but some incidence of colorectal carcinoma (Bodaghi et al, 2005;Damin et al, 2007;Motlagh et al, 2007;Chen et al, 2012). This diversity has been explained according to possibility of contamination in sample preparation and testing and different frequency of HPV infection between populations which may be affected of high-risk sexual behaviors (Bodaghi et al, 2005;Burnett-Hartman et al, 2008;Burnett-Hartman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated HPV DNA in 46/72 (64%) 35 and 23/55 (42%) 36 of colorectal carcinoma, suggesting a role for HPV infection, particularly HPV type 16, in colorectal carcinogenesis. However, both of these studies also reported the presence of HPV DNA in a large proportion of histologically normal mucosa adjacent to the colorectal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although several investigators have found an association between HPV and colorectal carcinoma, [54][55][56] the role of HPV in carcinogenesis of the colon remains to be elucidated. 57 Morphologically, low-grade and high-grade HPVrelated squamous mucosal lesions are similar whether they occur in the anus or cervix.…”
Section: Histology Of Ain and Anal Cancermentioning
confidence: 99%